INFINITESIMAL FIELD SIZE HVL OF ISO 4037 NARROW SPECTRUM X-RAYS: SIMULATED RESULTS - Ngoc Thiem Le (Tạp chí Khoa học Đại học Đà Lạt)
Half-value layer (HVL) measurement is the method most often used to validate an X-ray reference field as defined in ISO 4037. This work presents Particle and Heavy Ion Transport code System (PHITS) simulated values of HVL and their standard deviations for an infinitesimal radiation field size. The HVL values, calculated from simulated values of air kerma at a detector position for various radiation field sizes, were extrapolated to an infinitesimal field size for different ISO 4037 narrow spectrum X-ray beam qualities at two distances from an X-ray source.